2014
DOI: 10.15740/has/au/9.3/306-310
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge level of beneficiary and non- beneficiary farmers about improved groundnut production technology

Abstract: The study was undertaken in Banaskantha district of Gujarat to know the knowledge level of farmers about groundnut production technologies under FLD on a sample of 70 beneficiary and 70 non-beneficiary farmers. It was observed that maximum number of beneficiary farmers (55.72%) and non-beneficiary farmers (62.86%) had medium level of knowledge about groundnut production technologies, where as 35.71 per cent beneficiary farmers and 4.28 per cent non-beneficiary farmers had high level of knowledge. Significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Therefore, from the above fi ndings it can be concluded that education, mass media exposure, information seeking behaviour and information sharing behaviour were the important determinant of knowledge level of the benefi ciary, non-benefi ciary and overall respondents. The fi ndings are in conformity with the fi ndings of Pokar et. al.…”
Section: Conflicts Of Interestsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, from the above fi ndings it can be concluded that education, mass media exposure, information seeking behaviour and information sharing behaviour were the important determinant of knowledge level of the benefi ciary, non-benefi ciary and overall respondents. The fi ndings are in conformity with the fi ndings of Pokar et. al.…”
Section: Conflicts Of Interestsupporting
confidence: 91%
“…Comparative view of data pertaining to these three categories of farmers clearly bring to light that there was high level of knowledge among benefi ciary respondents, it means that there had been upward movement in the knowledge level of the farmers after receiving the benefi ts of CFLD. The fi ndings are supported by the fi ndings of Choudhary and Yadav (2012) who reported that majority of the respondents possessed medium level of knowledge about improved mungbean production technologies and also by the fi ndings of Pokar et. al.…”
Section: Resultsmentioning
confidence: 63%